Professionalism of Education Supervision - Siti Aisyah; Lilis Supriatin; Andri Hermawan; Dewi Nurdiyanti (Jurnal Edusci, 2026)
Background. The professionalism of education supervision is a strategic factor in ensuring the quality of education delivery, especially at the primary and secondary levels. Purpose. This study aims to analyze the level of professionalism of school supervisors in West Java Province and its impact on improving the quality of teachers and schools. This study uses a qualitative descriptive approach, supported by simple quantitative data from a survey of 75 school supervisors across five districts. Data were collected through in-depth interviews, observations, and questionnaires, based on supervisory competency indicators set out in Permendikbud Number 143 of 2014. Results. The results of the study show that the professional competence of supervisors in West Java is in the high category (82%), especially in the dimensions of academic and managerial supervision. However, the main challenge remains mastering digital technology and implementing continuous evaluation. Conclusion. The analysis also showed a positive correlation between the intensity of supervision and improvements in the quality of teachers' performance and in the achievement of school accreditation. Implementation. This research emphasizes the importance of capacity building and continuous professional development for education supervisors as quality agents in the regions.